Surface Structure of 4-Mercaptopyridine on Au(111): A New Dense Phase - Herrera, Santiago Esteban (2017)
4-Mercaptopyridine (4MPy) self-assembled on Au(111) has been studied by in situ electrochemical scanning tunneling microscopy (EC-STM) in HClO4, cyclic voltammetry, X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT). Samples prepared by varying the immersion time at constant concentration named short time (30 s) and long time (3 min) adsorption have been studied. Cyclic voltammetry and XPS showed that the chemistry of the adsorbed molecules does not depend on the adsorption time resulting in a well established chemisorbed thiol self-assembled monolayer on Au(111). EC-STM study of the short time adsorption sample revealed a new self-assembled structure after a cathodic desorption/readsorption sweep, which remains stable only if the potential is kept negative to the Au(111) zero charge potential (EPZC). DFT calculations have shown a correlation between the observed structure and a dense weakly adsorbed phase with a surface coverage of θ = 0.4 and a (5 × √3) lattice configuration. At potentials positive to the EPZC, the weakly adsorbed state becomes unstable, and a different structure is formed due to the chemisorption driven by the electrostatic interaction. Long time adsorption experiments, on the other hand, have shown the typical (5 × √3) structure with θ = 0.2 surface coverage (chemisorbed phase) and are stable over the whole potential range. The difference observed in long time and short time immersion can be explained by the optimization of molecular interactions during the self-assembly process.